Identification of UDP-glucuronosyltransferases involved in the metabolism of silymarin flavonolignans - Vrba, Jiří; Papoušková, Barbora; Lněničková, Kateřina; Kosina, Pavel; Křen, Vladimír; Ulrichová, Jitka (Journal of pharmaceutical and biomedical analysis, 2020)
Silybum marianum (milk thistle) is a medicinal plant used for producing the hepatoprotective remedy silymarin. Its main bioactive constituents, including silybin and related flavonolignans, can be metabolized directly by phase II conjugation reactions. This study was designed to identify UDP-glucuronosyltransferases (UGTs) involved in the glucuronidation of six silymarin flavonolignans, namely silybin A, silybin B, isosilybin A, isosilybin B, silychristin, and silydianin. UHPLC-MS analyses showed that all of the tested compounds, both individually and in silymarin, were glucuronidated by human liver microsomes, and that glucuronidation was the main metabolic transformation in human hepatocytes. Further, each compound was glucuronidated by multiple recombinant human UGT enzymes. UGTs 1A1, 1A3, 1A8 and 1A9 were able to conjugate all of the tested flavonolignans, and some of them were also metabolized by UGTs 1A6, 1A7, 1A10, 2B7 and 2B15. In contrast, no glucuronides were produced by UGTs 1A4, 2B4, 2B10 and 2B17. With silymarin, we found that UGT1A1 and, to a lesser extent UGT1A9, were primarily responsible for the glucuronidation of the flavonolignan constituents. It is concluded that the metabolism of silymarin flavonolignans may involve multiple UGT enzymes, of which UGT1A1 appears to play the major role in the glucuronidation. These results may be relevant for future research on the metabolism of flavonolignans in humans.
Keywords: hepatocyty; Glucuronides; dospělí; Microsomes; Metabolism; flavonolignany; Adult; Glucuronosyltransferase; Silybum marianum; lidé; Glucuronidation; Cytochrome P450; kultivované buňky; jaterní mikrozomy; silibinin; ostropestřec mariánský; Hepatocytes; Cells, Cultured; Male; silymarin; Silybin; Microsomes, Liver; glukuronosyltransferasa; glukuronidy; mužské pohlaví; Flavonolignans; UGT; Silymarin; Humans